The recent history of afferent stimulation modulates corticospinal excitability - Bonnesen, Marie Trolle; Fuglsang, Søren Asp; Siebner, Hartwig Roman; Christiansen, Lasse (NeuroImage (Orlando, Fla.), 2022)
Transcranial magnetic stimulation (TMS) is widely used to probe corticospinal excitability and fast sensorimotor integration in the primary motor hand area (M1-HAND). A conditioning electrical stimulus, applied to the contralateral hand, can suppress the motor evoked potential (MEP) elicited by TMS of M1-HAND when the afferent stimulus arrives in M1-HAND at the time of TMS. The magnitude of this short-latency afferent inhibition (SAI) is expressed as the ratio between the conditioned and unconditioned MEP amplitude. We hypothesized that corticospinal excitability and SAI are influenced by the recent history of peripheral electrical stimulation. In twenty healthy participants, we recorded MEPs from the right first dorsal interosseus muscle. MEPs were evoked by single-pulse TMS of the left M1-HAND alone (unconditioned TMS) or by TMS preceded by electrical stimulation of the right index finger (“homotopic” conditioning) or little finger (“heterotopic” conditioning). The three conditions were either pseudo-randomly intermixed or delivered in blocks in which a single condition was repeated five or ten times. MEP amplitudes and SAI magnitudes were compared using linear mixed-effect models and one-way ANOVAs. All stimulation protocols consistently produced SAI, which was stronger after homotopic stimulation. Randomly intermingling the three stimulation conditions reduced the relative magnitude of homotopic and heterotopic SAI as opposed to blocked stimulation. The apparent attenuation of SAI was caused by a suppression of the unconditioned but not the conditioned MEP amplitude during the randomly intermixed pattern. : The recent history of afferent stimulation modulates corticospinal excitability. This “history effect” impacts on the relative magnitude of SAI depending on how conditioned and unconditioned responses are intermixed and needs to be taken into consideration when probing afferent inhibition and corticospinal excitability.